Identifying a novel anticancer agent with microtubule-stabilizing effects through computational cell-based bioactivity prediction models and bioassays. Issue 6 (25th January 2019) - Luo, Yao; Zeng, Ranran; Guo, Qingqing; Xu, Jianrong; Sun, Xiaoou; Wang, Ling
Abstract : G03 is a novel anticancer agent with unusual microtubule-stabilizing effects. Abstract : We report the identification of 14 novel anticancer agents through established computational anticancer cell-based models. Among these novel hits, the compoundG03 exhibits stronger inhibitory effects on the proliferation of MCF-7, HepG2, MDA-MB-231, HCTT116, and HeLa as compared with the FDA-approved sorafenib, with IC50 values of 4.61, 3.20, 2.82, 2.98, and 2.90 μM, respectively. The tubulin protein was validated to be a target ofG03 using SPR, tubulin polymerization, immunofluorescence, and western blot assays.G03 is a novel structurally simple anticancer agent with unusual microtubule-stabilizing effects. Our study demonstrated the identification of bioactive small molecules by computational phenotypic modeling, which represents a feasible route toward innovative leads for chemical biology and medicinal chemistry.